Investigate the bond performance of basalt FRP bars under the effect of severe conditions - Mohamed Heshmat; Hany El-Shafie; Fareed Elgabbas (Scientific Reports)
Abstract This paper aims to evaluate the bond performance of basalt FRP bars under severe conditions such as salts, alkaline, and water. Specimens were tested under direct pull-out tensile load. The specimens were exposed to aggressive solutions at an elevated temperature of 60 °C to accelerate the degradation process. The parameters were the concrete compressive strength (CCS) (25, 45, and 60 MPa), the exposure condition (water, salts, and alkaline), and the exposure duration (30, 60, and 90 days). Seventy-two specimens were investigated in terms of bond strength, failure mechanism, and stress-slippage response. The most detrimental environment was the alkaline environment, while the salt environment had an insignificant effect on the bond strength. After 90 days of conditioning in the alkaline solution, the normalized bond strength had reduced by 17.29%, 12.74%, and 8.72% for specimens of concrete compressive strength (CCS) of 25 MPa, 45 MPa, and 60 MPa, respectively.